Water distribution and key aroma compounds in the process of beef roasting - Wang, Yong-Rui; Luo, Rui-Ming; Wang, Song-Lei (Frontiers in Nutrition, 2022)
The key aroma compounds and water distribution of the beef at different roasting times (0, 3, 6, 9, 12, 15 and 18 min) were identified and analyzed. The results showed that the L* value increased considerably before peaking and then decreased. On average, a* values decreased significantly first and then kept stable, while b* values increased first and then decreased. A total of 47 odorants were identified in all samples, including 14 alcohols, 18 aldehydes, 6 ketones, 1 ester, 3 acids, 4 heterocyclic compounds, and 1 other compound. Among them, 11 key aroma compounds were selected and aldehydes and alcohols predominantly contributed to the key aroma compounds. The fluidity of the water in the beef during the roasting process was decreased, and the water with a high degree of freedom migrated to the water with a low degree of freedom. The correlation analysis showed that water content and L* were negatively correlated with key aroma compounds of the samples, while M21 was positively correlated with key aroma compounds.